Preventive Effect of Glycine on 5-FU-Induced Oral Mucositis in Rats (Histological and Immunohistochemical Study) - Fatin L. Khaphi1 , Karim H.Al. Derawi2 , Maha K. Ibrahim3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
OM is the most popular side effects of chemotherapy and it’s commonly caused by 5-Fluorouracil (5-FU). This study was aimed to assess the impact of glycine as a new option of treatment on experimentally induced oral mucositis in adult male rats. Thirty two male rats (Rattus novergicus) were divided at random in to control group (8 rats), 5-FU untreated group and 5-FU-glycine treated group (12 animals each). OM model induced by chemotherapy was instituted by intraperitoneal injection of 5-FU (60 mgbody weight) on days 0, 5, 10, 15 and the dorsal tongue was scratched (days 3, 4) by needle with gauge 18 to induce mucositis. The rats in treated group were received a 2mgintraperitoneal injection of 5% glycine daily (day 0-20). All rats were scarified at day 21, dorsal tongue mucosa sample was removed, prepared and examine by using histological and immunohistochemical (PCNA and BCL-2 immunostining) analysis. Glycine can protect the dorsal tongue mucosa from 5-FU induced cytotoxicity and alleviated the associated damage. In 5-FU/glycine group, both of the PCNA and BCL-2 immune expression was significantly increased (p?0.05) in comparison with 5-FU untreated group. Glycine provides protection toward 5-Fluorouracil induced tongue mucositis. It show fast epithelial propagation and wound healing through its antioxidant, anti-inflammatory and cytoprotective features.